New opinion on the subtypes of poststroke depression in Chinese stroke survivors - Yue Y; Liu R; Cao Y; Wu Y; Zhang S; Li H; Zhu J; Jiang W; Wu A; Yuan Y (Neuropsychiatric Disease and Treatment, 2017)
Yingying Yue,1,2 Rui Liu,3 Yin Cao,4 Yanfeng Wu,5 Shining Zhang,6 Huajie Li,7 Jijun Zhu,8 Wenhao Jiang,1,2 Aiqin Wu,9 Yonggui Yuan1,2 1Department of Psychosomatics and Psychiatry, ZhongDa Hospital, School of Medicine, Southeast University, Nanjing, 2Institute of Psychosomatics, Medical school of Southeast university, Nanjing, 3School of Information Science and Engineering, Southeast University, Nanjing, 4Department of Neurology, Changzhou Second People’s Hospital Affiliated to Nanjing Medical University, Changzhou, 5Department of Neurology, The Second Affiliated Hospital of Nanjing Medical University, 6Department of Psychiatry, Nanjing Brain Hospital of Nanjing Medical University, Nanjing, 7Department of Neurology, Changzhou First People’s Hospital, Changzhou, 8Department of Neurology, Yancheng Third People’s Hospital, Yancheng, 9Department of Psychosomatics, The Affiliated First Hospital of Suzhou University, Suzhou, People’s Republic of China Aim: Poststroke depression (PSD) is the most common complication of stroke. However, some stroke survivors with depression cannot meet the diagnostic criteria of PSD. The aim of this study was to propose the new conception of stroke patients with depression and then make them to receive reasonable diagnosis and treatment. Methods: We first put forward the opinion that the general PSD should consist of PSD disorder (PSDD) and PSD symptoms (PSDS) according to the Diagnostic and Statistical Manual of Mental Disorder – Fifth Edition (DSM-5) and ZhongDa diagnostic criteria – first edition (ZD-1), respectively. The ZD-1 was established based on the suggestions of 65 Chinese chief doctors considering that the symptoms of PSDS might be different from those of PSDD and the duration of DSM-5 was too strict. Then, 166 stroke inpatients were recruited, and the study was conducted using the diagnosis and classification of PSD to verify the new concept. Results: A total of 24 (14.46%) and 80 (48.19%) stroke patients were diagnosed with PSDD and PSDS, respectively, according to individual diagnosis criteria. Moreover, patients meeting the diagnostic criteria of PSDD should satisfy the criteria of PSDS first. The distribution frequencies of depressive symptoms were different, which suggested that there might be discrepant depressive symptoms between PSDS and PSDD. Conclusion: The present study proposes new opinion about the classification and diagnosis of depression in stroke survivors. The definition and criteria of PSDS are beneficial to explore phenomenological consistency and provide useful information for early recognition and appropriate interventions. Keywords: poststroke depression, subtypes, diagnostic criteria